Temoa: An Open Educational Resources Portal to seek, investigate and inquire - Marcela Georgina Gómez-Zermeño; Lorena Yadira Alemán de la Garza (Open Praxis, 2015)
Temoa is a distributor of knowledge that provides a multilingual public catalog of collections of Open Educational Resources (OER). Temoa seeks to support the educational community to find the resources and materials that meet their needs for teaching and learning, through a specialized search system and collaborative social tools. Temoa was established after the need to expand educational coverage in the world, and specifically in developing countries. This paper aims to analyze the system of classification and metadata schemes of Temoa. Interviews were carried out to obtain information. Results shows Temoa’s cataloging process: reviewing OER design, form, and content; the actors participating in the process. We conclude that Temoa is a useful tool that helps to integrate OER into teaching practices, encouraging Knowledge Transfer and Dissemination of innovative educational strategies.